Financial Freedom or Just a Dream? The Effect of Financial Planning on the Financial Wellbeing of Gen Z Employees in West Java - Junet Kaswoto; Eko Sudarmanto (Sciences du Nord Economics and Business, 2025)
This study explores the impact of financial planning and financial literacy on the financial well-being of Generation Z employees in West Java, Indonesia. Utilizing a quantitative research design, data were collected from 300 respondents using a Likert scale (1-5) and analyzed with Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results reveal that both financial planning and financial literacy significantly and positively influence financial well-being, with a combined explanatory power of 62%. Financial planning emerged as a critical determinant, emphasizing the importance of structured approaches to financial goal-setting and management. Similarly, financial literacy enhances decision-making capabilities, enabling employees to navigate financial challenges effectively. These findings underscore the necessity for targeted interventions, including financial education and planning tools, to support Generation Z in achieving long-term financial stability and satisfaction.